2011
DOI: 10.1016/j.jvs.2010.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access for hemodialysis in the elderly

Abstract: In our experience, the creation of permanent hemodialysis access in the elderly with AVF is not only possible but also proved to have a short hospital stay, high patency rates, and an acceptable rate of further intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 23 publications
(20 reference statements)
4
45
1
Order By: Relevance
“…The only reason for technique failure was vascular thrombosis in both groups [8] . Similar reports have been published by Swindlehurst et al [101] , according to which the creation of permanent HD access in the elderly with AVF is not only possible but also proved to have a short hospital stay, high patency rates and an acceptable rate of further intervention. Desilva et al [102] state that, while specific subgroups in the HD population exist where use of fistulas and grafts at time of dialysis initiation is not of proven statistical benefit to survival, elderly HD patients with comorbidities still appear to benefit from the use of fistulas and grafts.…”
Section: Mortality and Morbidity Of Vascular Accesssupporting
confidence: 83%
“…The only reason for technique failure was vascular thrombosis in both groups [8] . Similar reports have been published by Swindlehurst et al [101] , according to which the creation of permanent HD access in the elderly with AVF is not only possible but also proved to have a short hospital stay, high patency rates and an acceptable rate of further intervention. Desilva et al [102] state that, while specific subgroups in the HD population exist where use of fistulas and grafts at time of dialysis initiation is not of proven statistical benefit to survival, elderly HD patients with comorbidities still appear to benefit from the use of fistulas and grafts.…”
Section: Mortality and Morbidity Of Vascular Accesssupporting
confidence: 83%
“…(Figure 13) Our findings suggested that there was no difference in vascular access complications across age groups and the survival of the first AV fistula was independent of age [8]. Similar reports have been published by Swindlehurst N et all according to which the creation of permanent hemodialysis access in the elderly with AVF is not only possible but also proved to have a short hospital stay, high patency rates, and an acceptable rate of further intervention [90]. 16 % more likely to be hospitalized, overall, than men.…”
Section: Vascular Access Complications and Survivalsupporting
confidence: 80%
“…According to our data patients over 80 years tend to have even slightly less shunt complications than younger patients. Neither did other authors find differences in the elderly [21,22], and especially in patients aged over 80 years [23,24]. Nadeau-Fredette et al reported a higher rate of primary AV-fistula failure in patients over 80 years.…”
Section: Discussionmentioning
confidence: 99%
“…But the subsequent primary patency was similar [25]. Swindlehurst et al found that grafts in the elderly had a higher cumulative patency compared to patients aged below 65 [22]. Early and close cooperation with vascular surgeons can help avoiding catheters.…”
Section: Discussionmentioning
confidence: 99%